Influence of white blood cell count trajectories on the risk of differentiation syndrome during induction therapy with all-trans-retinoic acid and arsenic trioxide in pediatric acute promyelocytic leukemia - Fu, Houxin; Liu, Yuchen; Hu, Shaoyan (Frontiers in Pediatrics, 2026)
ObjectiveThis study aims to investigate the association between early dynamic trajectories of white blood cell (WBC) count and the risk of differentiation syndrome (DS) during induction therapy with All-trans-retinoic Acid (ATRA) combined with arsenic trioxide (ATO) in pediatric patients with acute promyelocytic leukemia (APL).MethodsA retrospective cohort of pediatric APL patients treated with ATRA and ATO induction therapy between January 2016 and December 2024 is analyzed. Latent growth mixture modeling (LGMM) is employed to identify distinct WBC count trajectories over the first seven days of induction therapy. DS is diagnosed according to Frankel's criteria. Logistic regression analyses are performed to evaluate associations between WBC trajectory classes and the occurrence of DS, treatment-related complications, and transfusion requirements.ResultsA total of 93 patients are included, with an overall incidence of DS of 40.9% during induction therapy. Four distinct WBC trajectory classes are identified: Class 1 (high-level increasing group), Class 2 (high-level decreasing group), Class 3 (persistently low-level group), and Class 4 (low-level increasing group). After adjustment for potential confounders, patients in Class 1 (OR: 11.37, 95% CI: 1.17–124.71) and Class 4 (OR: 8.34, 95% CI: 1.94–35.92) remain at significantly increased risk of DS compared to those in Class 3, while no significant difference in DS risk is observed between Class 2 and Class 3. Furthermore, patients in Class 1 require more frequent transfusion support, including red blood cells, platelets, and plasma (p < 0.001) during induction therapy.ConclusionThe trajectory of WBC count during ATRA and ATO induction therapy may serve as an indicator for predicting the risk of DS in pediatric APL patients.